A combined zircon Hf isotope and whole-rock Nd and Sr isotopes study of Carboniferous A-type granites, Sierras Pampeanas of Argentina. (June 2020) - Dahlquist, Juan A.; Galindo, Carmen; Morales Cámera, Matías M.; Moreno, Juan A.; Alasino, Pablo H.; Basei, Miguel A.S.; Macchioli Grande, Marcos
Abstract: We report new whole-rock Nd and Sr isotope data for two strongly peraluminous and one slightly peraluminous Carboniferous A-type granitic plutons in the eastern Sierras Pampeanas of Argentina. Our study also integrates previous petrological and geochemical information with in situ U–Pb and Hf isotope data from magmatic and inherited zircon. Strongly peraluminous samples have pronounced negative εNdt values (−7.6 and −7.0) and very high ( 87 Sr/ 86 Sr)t values (0.728778 and 0.747092). These are similar to isotope compositions reported for the Puncoviscan Series, a metasedimentary sequence metamorphosed during the Lower Cambrian and intruded by these granites. Nd and Sr isotope data for the slightly peraluminous sample (εNdt  = −3.5 and 87 Sr/ 86 Srt  = 0.708074), together with previously reported petrological and geochemical data, indicate that the basement of the Sierras de Córdoba participated in the generation of the parental magma. The new data are not easily reconciled with the positive zircon εHft values previously reported for these samples, which suggest dominantly juvenile material in the source. We propose that Hf was transferred from inherited zircon toward the magmatic rim, without complete isotopic homogenization with the magma, as has been hypothesized in previous works. Our results reveal that the indiscriminate use of Hf databases can lead to false inference of crustal growth by mantle addition through time and misleading comparisons between granitic rocks worldwide. Highlights: Whole-rock Nd and Sr isotope data from peraluminous A-type granites are reported. Nd and Sr isotope produce opposite results for granites with positive εHft values. We propose transfer of Hf from inherited zircon toward the magmatic rim. Indiscriminate use of Hf databases can lead to false inference of crustal growth.